1996
DOI: 10.1051/epn/19962705179
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Holography with Atom Resolution

Abstract: A new concept based on well-established fundamental principles allows the high-resolution holographic imaging of atoms inside bulk cystals using X-rays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Sensitive and low‐dose X‐ray detection is vital in medicine, industry, and science. [ 1–3 ] Two major technologies are used to construct X‐ray detectors, namely, indirect and direct approaches, [ 4–11 ] as illustrated in Figure a and Figure S1a, Supporting Information. Comparatively, the direct approach that involves the one‐step creation of electron–hole pairs (EHPs) in a semiconductor photoconductor through the absorption of X‐ray photons is more compelling owing to its high photoelectric conversion efficiency and high intrinsic spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive and low‐dose X‐ray detection is vital in medicine, industry, and science. [ 1–3 ] Two major technologies are used to construct X‐ray detectors, namely, indirect and direct approaches, [ 4–11 ] as illustrated in Figure a and Figure S1a, Supporting Information. Comparatively, the direct approach that involves the one‐step creation of electron–hole pairs (EHPs) in a semiconductor photoconductor through the absorption of X‐ray photons is more compelling owing to its high photoelectric conversion efficiency and high intrinsic spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The solution for the first problem was given by the present authors (Tegze and Faigel 1991). A few years later the second problem was also solved by careful experimental arrangements and the 3D order of Sr atoms was reconstructed first in SrTiO 3 (Tegze and Faigel 1996) and then the two-dimensional (2D) picture of the Fe atoms in the basal plane of Fe 2 O 3 (Gog et al 1996) was reported. The latest experimental development in the field of inside source holography was the use of gamma rays for holographic imaging.…”
Section: Introductionmentioning
confidence: 93%
“…The first x-ray fluorescence holography experiment was performed by the present authors in 1995 (Tegze and Faigel 1996). The schematic view of the experimental set-up is shown in figure 5.…”
Section: Hard X-ray Holography With Inside Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…of the source and its conservation with time. Moving towards shorter wavelengths (towards water window and 1 keY radiation), where applications are more likely to occur [7,8] will also represent a major step forward.…”
Section: Introductionmentioning
confidence: 99%